Association between adverse childhood experiences with chronic kidney diseases in middle-aged and older adults in mainland China - Ziyi Shen; Chengcheng Li; Yan Fang; Hongxu Chen; Yongxia Song; Junling Cui; Xin Luo; Yanchang Liu; Fei Zhong; Jingfang Hong (Scientific Reports, 2025)
Abstract Adverse childhood experiences (ACEs) among middle-aged and elderly individuals may influence the subsequent occurrence of chronic kidney disease (CKD). We aim to investigate the association between ACEs and CKD among the middle-aged and elderly populations in China. The prospective cohort longitudinal study examined baseline data from the China Health and Retirement Longitudinal Study (CHARLS) from June 1 to December 31, 2014. Subsequent follow-up surveys were conducted in 2015, 2018, and 2020. The study population consisted of 4063 participants aged at least 45 years, who had CKD data and information on the 16 complete ACEs indicators included in this study. Utilizing correlation analysis to explore the relationship between CKD and the total score of ACEs, as well as the three dimensions (Conventional ACEs, Expanded ACEs, and New ACEs), along with specific items. The correlation between individual ACEs, disease-related factors, and CKD was examined using binary logistic regression models. Valuable diagnostic factors were then identified through the use of ROC curves. A Cox proportional hazards regression model, with age as the timescale and ACEs groups as covariates, was established to investigate the relationship between age-related CKD occurrence and ACE groups as individuals aged. Among the 4063 participants included in the analysis, in patients with CKD, the male proportion is 85 (64.9%), and the female proportion is 46 (35.1%). Of the participants, 2332 experienced at least two Conventional ACEs, 3786 experienced at least two Expanded ACEs, and 2774 experienced at least one New ACE. Factors influencing the occurrence of CKD in participants included Conventional ACEs 5 (OR 1.742; 95% CI 1.115–2.721; P = 0.015), Conventional ACEs 6 (OR 1.581; 95% CI 1.024–2.442; P = 0.039), Conventional ACEs 9 (OR 2.190; 95% CI 1.288–3.725; P = 0.004), Expanded ACEs 3 (OR 0.195; 95% CI 0.085–0.444; P < 0.001), memory-related disease (OR 3.297; 95% CI 1.140–9.538; P = 0.028), dyslipidemia (OR 2.536; 95% CI 1.521–4.230; P < 0.001), cancer (OR 6.369; 95% CI 2.464–16.461; P < 0.001), chronic lung disease (OR 2.261; 95% CI 1.091–4.684; P = 0.028), and liver disease (OR 3.050; 95% CI 1.432–6.497; P = 0.004). These three models showed significant statistical differences in CKD, the Conventional ACEs, and the New ACEs. In Model 1, 2, and 3, the risk was higher for individuals exposed to the Conventional ACEs group, indicating an increased likelihood of developing CKD, the risk was lower for individuals exposed to the New ACEs group, suggesting a reduced likelihood of developing CKD. ROC curve analysis of these variables showed that CA5, CA6, CA9, dyslipidemia had significant diagnostic value for the occurrence of CKD. The accuracy of diagnosis was CA5 (57.0%), CA6 (58.3%), CA9 (59.4%), and dyslipidemia (59.8%). This study, through longitudinal investigation, has identified potential links between ACEs and disease-related factors with CKD. These findings can still provide assistance to clinicians and public health administrators, helping them understand the association between ACEs and CKD, and offering theoretical support for their clinical decision-making or development of public health policies.